Analisis Dan Perancangan Sistem Informasi Pengelolaan Data Alumni Berbasis Web Pada SMK N 1 Kempas - Ramadhan, Fauzan purma; Sharipuddin; Effiyaldi, Effiyaldi (LPPM STIKOM Dinamika Bangsa, 2025)
The management of alumni data that is still conducted manually at SMKN 1 Kempas has led to various issues, such as long processing times and difficulties in tracking alumni data. This study aims to develop an Alumni Data Management Information System that can facilitate both alumni and school officials in managing this data. The information system is developed using the PHP programming language and the CodeIgniter framework, following the Waterfall method. This Waterfall method includes stages of requirements analysis, system design, implementation, testing, and maintenance. The system is designed to enable school officials to manage and monitor data efficiently, as well as to simplify the data entry process for alumni. The results of the system implementation indicate an increase in efficiency in managing alumni data, with faster processing times. Additionally, this system makes it easier for alumni to input their data and assists school officials in tracking and managing alumni data. Thus, the developed Alumni Data Management Information System successfully achieves its goal of facilitating the process of managing alumni data at SMKN 1 Kempas.